The Psychological States of Beggars in Malaysia: Happiness, Subjective Well-Being, and Gratitude - Lim, L. Gin; Kalaivanan, Syasyila; Zhooriyati, S. M. (UNIMAS Publisher, 2021)
The economic downturn causes a fluctuation of Malaysian beggars with disrupted psychological states. The research focuses on happiness, subjective well-being, and gratitude among the beggars in Kuala Lumpur and Selangor. Ten beggars participated in an in-depth interview. Their selection was based on a purposive sampling technique. Findings show that with life satisfaction and maintained health conditions, they would be contented. Intolerable circumstances currently made the beggars wishing they could restart an ideal life to restore their subjective well-being. Amidst gratefulness, beggars tend to wake up with an appreciation for every little thing. However, the limited psychological care given has caused the number of beggars to escalate. The number of beggars would dwindle by appraising the public with what they necessitate through an awareness brought by findings from the study.